Wilkie syndrome as a diagnostic challenge in intestinal obstruction: case report - Rodriguez-Benites, Arnold Frank (2024)
Wilkie syndrome is a rare pathology that generates intestinal obstruction due to a of the aortomesenteric angle compromising the third portion of the a case of an 18-year-old female patient, diagnosed with Wilkie syndrome, with symptoms of intestinal obstruction and weight loss. The diagnosis was made CT. Wilkie syndrome is a rare pathology, which becomes a diagnostic challenge presents a similar picture to other more common pathologies. We recommend be suspected in the presence of duodenal obstruction.